TEACHING AND LEARNING QUALITY (DESCRIPTIVE STUDY ON ADMINISTRATION MAGISTER PROGRAM, FACULTY OF EDUCATION, UNIVERSITY OF BENGKULU, INDONESIA) - Rohiat Rohiat (International Journal of Educational Management and Innovation, 2020)
Almost all education and higher education are ready to face the 21st century, which is digital and millennial. This study aims to describe the teaching and learning quality of the Administration Magister Program facing the 21st century. This study used descriptive qualitative methods. The research has conducted at the Administration Magister Program, Faculty of Education, University of Bengkulu, Indonesia. Data collection techniques with checklists, interviews, observation, and documentation studies. Data were analyzed quantitatively and qualitatively. The results show that teaching and learning not yet develop motivation students to learn hard, develop critical thinking. Still dominated by lecturers with the lecture method, assignment, students, and lecturers have not triggered to improve themselves directly and not yet close the way of learning in the 4.0 revolution era. Students have not motivated to do their best so that the learning outcome will be maximal. The lecturer model learning behavior and teaches based on scenarios that have made that are not yet flexible for enjoyable learning. The lecturer has not yet acted as a facilitator in learning—suggestions to heads of education offices immediately given training on learning in the industrial revolution era 4.0. Lecturers and students can develop 21st-century learning.